Die Este und das Heilige Römische Reich im langen 16. Jahrhundert - Taddei, Elena (2020)
As one of the eldest Italian dynasties, the Este used not only their feudal bonding but also their cultural power, their network and relationship with Catholic and Protestant princes expressed in gifts, marriage projects and patronage for surviving in the conflicts of 16th century Italy and gaining help and support for their goals (investiture, precedence, titles).